Specific Species DNA Amplification as a Halal Authentication Method in Sausage Based on Genetic Markers - Purnomo, Nurul; Mansur, Musdalifa; Nugraha, Angga; Dagong, Muh. Ihsan A.; Natsir, Asmuddin (Faculty of Agriculture, 2023)
ABSTRACT. Sausage is a processed meat food that is susceptible to counterfeiting by mixing non-halal meat, so a valid, fast and cheap halal authentication method is needed for sausages. This study aims to determine the specific species genes of Cytochrome-b in target DNA amplification as a halal authentication method in sausages. In this study, the samples used were beef sausage, chicken sausage, and pork sausage. The stages of this research consisted of DNA purification, measuring DNA quality, amplifying object DNA using Cytochrome-b, electrophoresis, and visualization of the gel documentation. The DNA purification results from beef sausage, chicken sausage, and pork sausage respectively obtained concentrations of 3 (ng/l), 2.6 (ng/l), and 2.8 (ng/l), and purity of 1.15, 0.76, and 0.88. Meanwhile, DNA amplification produced fragments with lengths for beef sausage, chicken sausage, and pork sausage, namely the Cytochrome-b gene 274 bp, 227 bp, and 398 bp. Based on this study, it's concluded that the Cytochrome-b genes could amplify target DNA from beef sausage, chicken sausage, and pork sausage so that they could be used as gene markers for authenticating halal sausages.(Amplifikasi DNA Spesifik Spesies sebagai metode autentikasi halal pada sosis berdasarkan penanda genetic)ABSTRAK. Sosis merupakan makanan olahan daging yang rentan terhadap pemalsuan dengan mencampurkan daging non halal, sehingga diperlukan metode autentikasi halal yang valid, cepat dan murah untuk sosis. Penelitian ini bertujuan untuk mengetahui gen spesies spesifik Cytochrome-b pada amplifikasi DNA target sebagai metode autentikasi halal pada sosis. Dalam penelitian ini, sampel yang digunakan adalah sosis sapi, sosis ayam, dan sosis babi. Tahapan penelitian ini terdiri dari pemurnian DNA menggunakan Quick-DNA Plus Kits, Zymo Research, pengukuran kualitas DNA, amplifikasi pada DNA target menggunakan gen Cytochrome-b, elektroforesis, dan visualisasi pada gel dokumentasi. Hasil pemurnian DNA sosis sapi, sosis ayam, dan sosis babi masing-masing diperoleh konsentrasi 3 (ng/l), 2,6 (ng/l), dan 2,8 (ng/l), dan kemurnian 1,15, 0,76, dan 0,88. Sedangkan amplifikasi DNA menghasilkan fragmen dengan panjang untuk sosis sapi, sosis ayam, dan sosis babi yaitu gen Cytochrome-b 274 bp, 227 bp, dan 398 bp. Berdasarkan penelitian ini, disimpulkan bahwa gen Cytochrome-b dapat mengamplifikasi DNA target dari sosis sapi, sosis ayam, dan sosis babi sehingga dapat digunakan sebagai penanda gen untuk autentikasi sosis halal.